Carbon capture simulation using ejectors for waste heat upgrading. (1st April 2016) - Reddick, Christopher; Sorin, Mikhail; Sapoundjiev, Hristo; Aidoun, Zine
Abstract: Reducing the valuable energy consumption of solvent regeneration remains the biggest technical challenge to full-scale deployment of post-combustion carbon capture. Aspen Plus modeling is applied to validate the new application of ejectors to upgrade external waste heat in the conventional absorption and desorption process for carbon capture. In this application, ejectors upgrade external waste heat with the goal of reducing the quantity of valuable turbine steam required to regenerate the solvent. The energy consumption of the base case capture process in this study is within the range of published data. The reference solvent is 20% wt. MEA (monoethanolamine). Three strategies for producing the ejector secondary steam are evaluated. Producing the ejector secondary steam from either the stripping column condensate or from the lean solvent are viable options, showing respectively valuable energy savings of 10 and 14%. In both cases the potential valuable energy reductions are limited by the finite amount of condensate available to create the ejector primary steam. Using the rich solvent stream to produce the ejector secondary stream does not reduce the valuable energy consumption. The choice of preheating the ejector primary fluid by means of waste heat or by heat integration is also discussed. Highlights: A coal fired post-combustion CO2 absorption/desorption capture process is modeled. Aspen Plus rate-based modeling is applied to base case and ejector enhanced cases. Three strategies to upgrade external waste heat using ejectors are compared. Solvent regeneration heat duty of base case was consistent with published data. Optimal ejector integration permits 10–14% reduction in valuable turbine steam.